Fprint a fingerprint recognition utility - Almoradie, Joel (1999)
Fingerprint recognition is a thing used by police to track down the criminals of a particular crime. When fingerprints are left at a crime scene, police acquire the said prints and a forensics expert compares the fingerprint to the prints that are found in police records. The manual method of matching fingerprints is usually slow, and it is difficult to determine a match from a large database. These are the reasons why fingerprints recognition is done by using a computer to match prints. The study of fingerprints recognition has been extensive. The research group had performed a study on the performances of the fingerprint recognition algorithms researched. The research group found out that even if the algorithms have some good performance on noise-free fingerprint samples, all have a difficult time handling fingerprints that contain a lot of noise. In this paper, the group used the algorithms researched and also proposed an algorithm that has a possibility of handling noise. It has been found out that there is a satisfactory performance when the proposed algorithm was applied to the noisy fingerprints. But since noise is present, a lot of mismatches occur because of the large quantity of noise. The group also explains how the algorithm could be improved.